2015
DOI: 10.1016/j.breast.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic breast density: Predictive value for pathological response to neoadjuvant chemotherapy in breast cancer patients

Abstract: Low mammographic BD, low BMI and early clinical stage were associated with improved pCR rate and lower pathological stage after neoadjuvant chemotherapy. BD had more pronounced association with response to chemotherapy after adjustment with BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
(36 reference statements)
1
24
0
Order By: Relevance
“…Differences were largest among postmenopausal and HR− patients [36]. Several other studies have associated lower BMI with higher rates of pCR [37]. Weight gain during neoadjuvant chemotherapy has not been associated with pCR [38], except perhaps in subgroups of women who were normal/underweight or postmenopausal at baseline, where it was associated with higher pCR rates [39].…”
Section: Discussionmentioning
confidence: 99%
“…Differences were largest among postmenopausal and HR− patients [36]. Several other studies have associated lower BMI with higher rates of pCR [37]. Weight gain during neoadjuvant chemotherapy has not been associated with pCR [38], except perhaps in subgroups of women who were normal/underweight or postmenopausal at baseline, where it was associated with higher pCR rates [39].…”
Section: Discussionmentioning
confidence: 99%
“…187,188 Breast density can also be exploited as an intermediate endpoint in studies on breast cancer etiology. Finally, information on breast density has recently proved useful to predict the pathologic response to neoadjuvant chemo- 189 or endocrine therapy. 190 As mentioned above, x-ray mammography is the gold standard for the assessment of breast density and the method that is generally applied in clinical practice.…”
Section: Assessment Of Breast Density and Estimate Of Cancer Riskmentioning
confidence: 99%
“…Furthermore, change in MD on the time scale of weeks or months has potential as a predictive marker of response of women to antiestrogens used in both chemoprevention in the high risk setting, or as an adjuvant therapy for oestrogen receptor-positive breast cancers [8,9]. Recent studies have indicated that the potential use of assessing change in MD as a predictive biomarker may also extend to other breast cancer therapies [10]. Therefore, high-frequency observation of MD may find utility in monitoring treatment response.…”
Section: Introductionmentioning
confidence: 99%